Octahedral Hexachloro Environment of Dy3+ with Slow Magnetic Relaxation and Luminescent Properties. Issue 22 (26th May 2021) - Benamara, Nesrine; Diop, Mayoro; Leuvrey, Cédric; Lenertz, Marc; Gilliot, Pierre; Gallart, Mathieu; Bolvin, Hélène; Setifi, Fatima; Rogez, Guillaume; Rabu, Pierre; Delahaye, Emilie
Abstract: The compound [BiCNIm]3 [DyCl6 ] was synthesized from a nitrile‐functionalized imidazolium ionic liquid [BiCNIm][Cl] and DyCl3  ⋅ 6H2 O in acetonitrile using solvothermal conditions. Structural characterization reveals that the Dy 3+ ions are in a quasi‐regular octahedral environment, formed by six chloride anions. The magnetic study indicates that this mononuclear compound exhibits a Single Ion Magnet behaviour. This behaviour is compared to that of other mononuclear compounds containing Dy 3+ ions in various octahedral environment. Abstract : A new compound containing octahedral [DyCl6 ] 3− entities has been synthesized solvothermally in presence of nitrile‐functionalized ionic liquid and its luminescent and magnetic properties have been studied. A Single Ion Magnet behaviour is observed which is compared to that of other rare‐earth compounds exhibiting similar environment.